Analisis Peserta Didik Terhadap Video Demonstrasi Praktikum IPA SMP/MTs Berorientasi Berpikir Kritis pada Materi Kalor dan Perpindahannya - Radhia Til Hannoum; Arief Muttaqiin (Department of Science Education, 2023)
Critical thinking skills are an important component of learning outcomes that students need to have. Critical thinking skills need to be trained during the learning process, thus increasing critical thinking skills can be increased. Through a video demonstration of a science practicum with critical thinking orientation, there is material of Heat and Transfer, it is hoped that it can become a learning medium that can train students' critical thinking skills. The development model used is the Plomp development model through three stages (Preliminary research, Prototyping stage and Assessment phase). This article contains only one stage of the Plomp development model, namely the Preliminary research stage. A student analysis questionnaire was given to 32 students at SMP Negeri 7 Padang to find out the need for a video demonstration of science practicum oriented critical thinking based on the perspective of students as users.